Hull Form Characteristics of Traditionally Fishing Vessel < 5 GT at Karangantu Archipelago Fishing Port - Hery Sutrawan Nurdin; Ani Rahmawati (Jurnal Perikanan dan Kelautan, 2021)
Karangantu Archipelago Fishing Port (PPN Karangantu) is one centre of fishery activity in Banten Province with various socio-cultural backgrounds of fishermen. One of the factors that influence the design characteristics (hull form) of fishing vessels is related to the socio-cultural community. Therefore, it is necessary to study the characteristics of the traditional ship design (<5GT) operating in PPN Karangantu. The research was conducted in August-October 2018 at PPN Karangantu. Data was collected using survey methods, field observations and interviews. The number of samples used as many as 25 units of fishing vessel with consideration of size, type of fishing gear, and ship design. Data analysis was carried out in a descriptive comparative method. The results showed that ships with a size of <5GT were a group of static gear and towed/dragged gear. There are two transversely hull forms, namely U bottom and round bottom. As for the longitudinally hull shape, it consists of a transom shape (type A and type B) and double pointed.